A Dense Infestation of Round Pits in the Irregular Echinoid Hemipneustes striatoradiatus (Leske) from the Maastrichtian of the Netherlands. Issue 1 (2nd January 2018) - Donovan, Stephen K.; Jagt, John W. M.; Langeveld, Marinus
ABSTRACT: A test of the holasteroid echinoid Hemipneustes striatoradiatus (Leske) from the upper Meerssen Member (subunit IVf-6; Maastricht Formation) in the type area of the Maastrichtian Stage (Late Cretaceous) was infested by 170 non-penetrative pits assigned to Oichnus excavatus (Donovan and Jagt). The echinoid is assumed to have been alive at that time. The distribution of pits is approximately bilaterally symmetrical and mainly supraambital; pits on the oral surface may have been carried subambitally by echinoid plate growth. Many pits are comparatively shallow; they probably were partly filled by the echinoid after death of the pit-forming organisms. The area around the periproct is devoid of pits as is the anterior ambulacrum (amb III). The latter was probably kept free of larval pit-formers by the tube feet; other ambulacra, with tube feet adapted for respiration, lacked such defense.